The analysis of students’ mathematical representation errors in solving word problem related to graph - Rahmah Johar; Khairiyah Rahma Lubis (Jurnal Riset Pendidikan Matematika, 2018)
The skills of reading, interpreting and constructing graphs are important for students. These skills are related to mathematical representation. The purpose of this study is to analyze Grade 8 students’ representation errors in solving word problems related to graphs in one of junior high schools in Banda Aceh, Indonesia. The data were obtained based on a mathematics test administered to 36 students and a short interview conducted for five selected students. The test consisted of eight problems adapted from four contexts of PISA problems related to graph. Students’ representation errors were classified based on the errors of changing one representation to another representation, such as visual to verbal, visual to symbolic, visual to visual and verbal to visual. The results reveal that representation errors are not solely influenced by the types of representation. It is indicated by the questions with similar representation resulted in a different percentage of students committing representation errors. In general, the students’ representation errors are due to the fact that students not being familiar with the problems requiring representation; students not being used to solve PISA context problems and word problems; as well as the teachers’ time constraint in teaching non-routine problems.